KARAKTERISTIK DAN DAYA TERIMA BUBUK INSTAN CAMPURAN TEPUNG KECAMBAH JAGUNG, TEPUNG TEMPE, DAN TEPUNG WORTEL SEBAGAI MAKANAN PENDAMPING ASI - Siti Sundari Putri; Jumirah .; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Infants whose entering the age of 6-24 months need a complementary foods to fulfill their daily nutritional needs. Recommended complementary foods are coming from local food that was highly nutritious, easily obtainable, and cereal-based, such as corn, tempeh, and carrot. The purpose of this study was to determine the characteristics and acceptance of powdered instant from flour corn sprouts, tempeh flour, carrot flour as complementary foods. This study was experimental study, using a completely randomized design, with three factors and two treatment, instant powder of flour corn sprouts, tempeh flour, carrot flour with ratio 50%: 40%: 10% and 55%: 40%: 5%. The mixture was made base on the adequacy of infant required nutrients 6-12 months. Panelists in this study were 7-12 months infants whose accompanied by his mother as many as 30 people. Test by organoleptic test and acceptence test data was analyzed by independent t test. The results showed that the organoleptic test of the color, flavor, and texture of the most preferred was powdered instant of flour corn sprouts 55%, tempeh flour 40%, and flour carrot 10%. While both instant powder aroma less preffered. Based on the analysis, there are differences in color and texture on both the instant powder. It was suggested to consumers to pay attention to the portion size of instant powder and advised to consume a wide variety of foodstuffs. Keywords: complementary foods, corn sprouts flour, tempeh flour, carrot flour, acceptability test